α-Mangostin Mediated Pharmacological Modulation of Hepatic Carbohydrate Metabolism in Diabetes Induced Wistar Rat - Vikas Kumar; Prakash Chandra Bhatt; Gaurav Kaithwas; Mohd Rashid; F.A. Al-abbasi; Jalaluddin A.J. Khan; Firoz Anwar; Amita Verma (Beni-Suef University Journal of Basic and Applied Sciences, 2016)
Garcinia mangostana L. (Fruit) has been commonly used as folklore drug in the treatment of various types of diseases. The present experiment was designed to evaluate the potential effect of α-mangostin mediated pharmacological modulation of hepatic carbohydrate metabolism in streptozotocin (STZ) induced diabetic rats. Oral glucose tolerance test (OGTT) was performed in normoglycemic rats. Single intraperitoneal injection of STZ (60 mg/kg, body weight) was used for induction the diabetes in Swiss albino (Wistar strain) rats. The rats were divided into different groups. Blood glucose level, body weight, insulin, glycated hemoglobin and hemoglobin levels were recorded at regular intervals. Biochemical parameters, liver enzymes, lipid profile, antioxidant parameters and inflammatory cytokine mediators were also scrutinized. Histopathology study of kidney, pancreas and liver were performed. The result of OGTT study depicted the better utilization of glucose in experimental rats. STZ induced diabetic rats treated with α-mangostin (25, 50 and 100 mg/kg, p.o.) and glibenclamide depicted the decline in the level of blood glucose; enhanced body weight and showed the better utilization of glucose by different organs. STZ induced diabetic rats treated with α-mangostin illustrated the increased level of plasma insulin, hemoglobin, hexokinase, HDL, total protein, SOD, CAT, GSH and declined level of glycated hemoglobin, fructose-1-6-biphosphatase, glucose-6-Phosphatase, TC, TG, LDL, VLDL, CRE, BUN, SGOT, SGPT, ALP and LPO at effective dose dependent manners. Histological study showed the inflamed blood vessels in diabetic kidney, which was less in α-mangostin treated rats; diabetic pancreatic showed the complete damage of β cells, islets, aciini and producing necrosis, but all damage was less obvious in α-mangostin treating group rats; diabetic liver showed the damage of hepatocytes as well as central vein but was less in treated groups. Considering the above results, α-mangostin shows potential to develop a medicine for diabetes, hyperlipidemia, renal and hepatic protection as combinational or mono-therapy.